A Story of Farmer-Monkey Interactions Towards Their Effects on Semi-Urban Migration and Livelihood - Lamichhane, Bishnu; Lamichhane, Barsha (Journal of Population and Development, 2024)
Migration involves changing residence due to economic, environmental, social, and political factors. Push factors such as poverty, unequal resource distribution, and labor demands compel people to relocate. In Nepal, low agricultural productivity serves as a significant push factor for migration, exacerbated by crop damage caused by wildlife. This crop damage results in economic losses for farmers, affecting their livelihoods and contributing to rural-to-urban migration patterns. A qualitative study was conducted in Likhu-6 in the Nuwakot district in October and November 2023. Participants were Nepalese residents aged 18 and above from Likhu Rural Municipality Ward No. 6. Farmers in the study encounter challenges due to the increasing monkey population, leading to crop damage and income reduction. This situation has compelled many farmers to relocate to semi-urban areas in search of alternative livelihoods. The presence of monkeys has diminished crop yields, causing financial strain on farmers and prompting them to abandon their farms for semi-urban areas. This migration has not only influenced the agricultural sector but also impacted the local economy and community dynamics. Efforts should be made to address the interactions between farmers and monkeys through deterrent measures and community-based solutions. Sustainable, long-term strategies are necessary to mitigate the impact of monkeys on farmers' livelihoods.